The relationship between the Ottawa Valve Collapse Scale (OVCS) and clinical outcomes in septoplasty patients - Phillip Staibano; James P. Bonaparte (Journal of Otolaryngology - Head and Neck Surgery)
Abstract The Ottawa Valve Collapse scale (OVCS) was developed to classify the severity of nasal valve collapse (NVC) in patients with nasal obstruction. The goal of this study was to determine, in patients who have nasal obstruction due to a septal deviation, whether those with a higher OVCS grade will have a reduced improvement in patient-centered clinical outcomes at one-year following septoplasty with inferior turbinate diathermy compared to those with a normal or lower OVCS grade. This study was a prospective study of 78 patients who completed an assessment using the NOSE questionnaire before and at one-year following the surgical intervention. A repeated-measures ANOVA was used to asses for differences in scores between OVCS groups. There was a significant improvement in NOSE scores one year post-septoplasty (p < 0.01). There was no difference in NOSE score improvement when comparing the grades of the OVCS at one-year (F = 0.09, p = 0.968). Though the OVCS was designed to categorize the severity of NVC preoperatively, there is no evidence that it is helpful in predicting which patients will demonstrate poor results following septoplasty. Future studies are required to further evaluate the OVCS and whether complimentary assessments will improve its clinical utility.